A Study to Assess the Effectiveness of Hot Water Therapy Among Elderly People with Joint Pain Living in Selected Areas of Mehsana District - Chaudhari Ankitaben Bhagavanbhai, N.Siva Subramanian,Patel Jaykumar Sanjaybhai, Patel Chelsi Vinodkumar, Patel Hani Vishnukumar, Patel Charmilkumar Arvindbhai, Patel Dishaben Nikeshkumar, Patel Esha Shaileshbhai; Patel Janavi Hareshbhai, Patel Jinal Ashvinkumar, Vaghela Payalben Tejmalji (South Eastern European Journal of Public Health, 2025)
Background: Articular pain is a common problem in the elderly, profoundly influencing their quality of life. Many treatment options are available, but non-drug methods like hot water therapy have come under scrutiny for their effectiveness in alleviating pain and functional gain. Methods: Quantitative research design was utilized, where 30 older people with joint pain were recruited. The data collection entailed demographic information and assessment of pain using a standard scale prior to and after the application of hot water. Descriptive statistics and inferential statistics were employed for data analysis, where frequency distribution, percentage analysis, mean, standard deviation, and chi-square test of association were applied. Results: The pre-test results indicated that 40% of the participants had mild pain, 26.66% moderate pain, and 16.66% severe pain. The post-test indicated a considerable decrease in pain with 66.66% having no pain, 16.66% having mild pain, and none with severe or worst pain. A statistically significant difference between pre-test and post-test pain scores was noted (p < 0.005), indicating the effectiveness of hot water therapy. Conclusion: Hot water treatment is an effective, safe, and readily available intervention to lower joint pain in joints in the elderly, enhancing their functional ability in performing activities of daily living. This research emphasizes the necessity of incorporating such non-pharmacological methods into regular nursing practice.